Comparative Genomics Analysis of Vibrio anguillarum Isolated from Lumpfish (Cyclopterus lumpus) in Newfoundland Reveal Novel Chromosomal Organizations - Ignacio Vasquez; Trung Cao; Setu Chakraborty; Hajarooba Gnanagobal; Nicole O’Brien; Jennifer Monk; Danny Boyce; Jillian D. Westcott; Javier Santander (Microorganisms, 2020)
Vibrio anguillarum is a Gram-negative marine pathogen causative agent of vibriosis in a wide range of hosts, including invertebrates and teleosts. Lumpfish (Cyclopterus lumpus), a native fish of the North Atlantic Ocean, is utilized as cleaner fish to control sea lice (Lepeophtheirus salmonis) infestations in the Atlantic salmon (Salmo salar) aquaculture industry. V. anguillarum is one of the most frequent bacterial pathogens affecting lumpfish. Here, we described the phenotype and genomic characteristics of V. anguillarum strain J360 isolated from infected cultured lumpfish in Newfoundland, Canada. Koch’s postulates determined in naïve lumpfish showed lethal acute vibriosis in lumpfish. The V. anguillarum J360 genome was shown to be composed of two chromosomes and two plasmids with a total genome size of 4.56 Mb with 44.85% G + C content. Phylogenetic and comparative analyses showed that V. anguillarum J360 is closely related to V. anguillarum strain VIB43, isolated in Scotland, with a 99.8% genome identity. Differences in the genomic organization were identified and associated with insertion sequence elements (ISs). Additionally, V. anguillarum J360 does not possess a pJM1-like plasmid, typically present in virulent isolates from the Pacific Ocean, suggesting that acquisition of this extrachromosomal element and the virulence of V. anguillarum J360 or other Atlantic isolates could increase.